Analysis of Service Quality and Customer Satisfaction for Umrah at PT. Allinma Universal Using the Potential Gain in Customer Value Method - Putra, Dimas Herlambang; Iriani, Iriani (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
PT. Allinma Universal is one of the providers of services for Umrah and Hajj travel with excellent facilities, making the pilgrimage journeys of customers comfortable. They also offer several packages at affordable prices. Customer satisfaction or dissatisfaction with Allinma Universal can occur at any time. This makes it necessary for PT. Allinma Universal to have a way to improve the quality of its services to ensure customer satisfaction. This study uses the method of potential profit in customer value to identify which attributes contribute to a decrease in customer satisfaction. The prioritized attribute for service quality improvement is attribute (Rs3), which is the speed of employee responses to customer questions with a PGCV index value of 10.36. The second attribute is (Re3), which involves providing accurate information about Umrah activities with a PGCV index value of 10.28. The third attribute is (Re1), which concerns complicated service procedures with a PGCV index value of 9.96. The recommendation given to Allinma Universal is to regularly evaluate the quality of its services. By doing so, they can identify areas where the perceived quality of services is lacking and work on improving them to enhance customer satisfaction.